Bakhita : a novel of the Saint of Sudan - Olmi, Véronique (Other Press, 2019)
"Inspired by the true story of a former slave who became a saint, this poignant novel explores how a human being can survive the obliteration of her identity, and how kindness and generosity can be born out of profound trauma. She recalls little of her childhood, not even her own name. She was barely seven years old when she was snatched by slave raiders from her village in the Darfur region of southern Sudan. In a cruel twist, they gave her the name that she will carry for the rest of her life: Bakhita, "the Lucky One" in Arabic. Sold and resold along the slave trade routes, Bakhita endures years of unspeakable abuse and terror. At age thirteen, at last, her life takes a turn when the Italian consul in Khartoum purchases her. A few years later, as chaos engulfs the capital, the consul returns to Italy, taking Bakhita with him. In this new land, another long and arduous journey begins--one that leads her onto a spiritual path for which she is still revered today. With rich, evocative language, Véronique Olmi immerses the reader in Bakhita's world--her unfathomable resilience, her stubborn desire to live, and her ability to turn toward the pain of others in spite of the terrible sufferings that she too must endure"--